Melt processable fluorinated Poly(aryl ether)s with low dielectric and good mechanical properties - Chang Yu; Yang Wang; Bo Jiang; Yang Yang; Jinxuan Han; Haibo Zhang; Yingshuang Shang (Polymer Testing)
The rapid development in high-frequency communication has raised the demand for intrinsic low dielectric materials. Fluorinated poly(aryl ether)s (FPAEs) have gained significant attention due to their excellent dielectric properties and heat resistance. However, current methods for preparing FPAE films involve organic solvents, which generate substantial waste during large-scale production. There is an urgent need for simpler and more efficient processing methods, such as injection molding or melt processing, to overcome the limitations of solvent-based approaches. In this study, FPAEs with different molecular weights were synthesized from decafluorobiphenyl (DFBP) and bisphenol AF. The melting index and rheological tests demonstrated that FPAEs exhibited good thermal stability and melt processing performance. Notably, the dielectric loss (Df) of FPAEs prepared by melt processing was significantly reduced (below 0.001) while their dielectric constant (Dk), mechanical strength, and flexibility remained comparable to those of FPAEs produced using solution processing. This study advances the melt processing of FPAEs with perfluorinated biphenyl groups, providing insights for large-scale production of low dielectric materials and broadening their potential applications in high-frequency communication.